Hepatic Microabscesses: A Unique Presentation of Herpes Simplex Virus Hepatitis. Issue 12 (3rd December 2021) - Olson, Kristin M.; Keim, Lauren M.; Holm, Tyson T.; Eichele, Derrick D.
ABSTRACT: Viral hepatitis caused by herpes simplex virus (HSV) infection occurs with a wide array of clinical presentations, making timely definitive diagnosis challenging. Immunosuppressed patients provide further complexity with an increased risk for severe infection and acute liver failure. We report a rare case of HSV hepatitis manifested as HSV type 1 and HSV type 2 (HSV-1 and 2) coinfection resulting in innumerable hepatic hypodensities with peripheral enhancement, suggestive of liver microabscesses. Initiation of antiviral therapy resulted in rapid recovery. The presence of hepatic hypodensities and acute liver injury should raise suspicion for HSV hepatitis in the immunocompromised host.